COMPARISON OF ANALYTICAL AND NUMERICAL COMPUTATION OF STRAIGHT, BROKEN AND CURVED BEAMS - MURČINKOVÁ, Zuzana (Trends in education, 2009)
The paper deals with comparison of computational approach and received results of shear force T, bending moment M, deformation w, φ and normal and shear stress σ, τ in (plane, compound) bending for straight, broken and curved beams. The various approaches to solution of mentioned problems indicate the possibility to use various approaches not only in computation. Also, it opens out the knowledge in branch of mechanical behaviour simulation of structures by use of software Pro/Mechanica or another.
Keywords: computation; beam; software; animation; visualization.